Innovation Policy in the New Legislative Period: A New Strategic Direction? - Daniel Feser (Wirtschaftsdienst)
Abstract The innovation policy of the new German government is at the threshold between the traditional and the transformative. In addition to company-oriented measures, current innovation policy in Germany is characterised above all by its orientation toward benefits for society as a whole. This represents an incremental development compared to the previous government. The focus is on reorienting knowledge transfer for societal transitions. Against this background, the innovation policy outlined in the coalition agreement contains traditional and transformative elements. Effects of the innovation policy arise in the areas of openness to technology, legitimacy of policy measures and participation.